ANALISIS PREPOSISI VON DAN AUS DALAM STUDI LINGUISTIK PRAGMATIK - Riska Sri Nur Padilah; Nuki Nurhani; Amir Amir (Jurusan Pendidikan Bahasa Jerman FPBS UPI, 2023)
In German there are several prepositions that have the same meaning, one of them is von and aus. However, both can be distinguished based on contextual meaning. Thereâ€™s a lot of prepositions of von and aus in novel â€œEin wahrer Apfel leuchtete am Himmelszeltâ€ by Sabine Peters in 2020, so that there is needed for research in the study of pragmatic linguistics. The study of speech acts in pragmatics aims to find out the meaning or meaning of the speech intended by the speaker. The purpose of this research is to find out and understand: 1) The types of speech acts of speech that contain the prepositions of von and aus in the data source, 2) Functions of speech acts of speech that contain the preposition of von and aus in the data source, and 3) The contextual meaning of the prepositions of von and aus in the data source. The method used in this research is descriptive analysis. Based on the results of this research, there are 65 speeches that contains the prepositions of von and aus. Among them, t here the types of locutionary speech act, most of the illocutionary speech act, and perlocutionary speech act. The function of speech acts found in this study functions as the most common assertives, declarative, disertives, expressives, and commissives. Furthermore, the contextual meaning of the preposition of aus in the speech that has been analyzed include 'from', 'out', and 'derived from', while the contextual meaning of von's preposition is 'from', 'by', 'belongs', and at the phrase â€œvon wegenâ€ means 'impossible', as well as the combined meaning of the phrase â€œvon mir ausâ€ which means â€˜I don't mindâ€™.